2020
DOI: 10.1111/codi.15153
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection in elective colonic and rectal resections: effect of oral antibiotics and mechanical bowel preparation compared with mechanical bowel preparation only

Abstract: Aim Surgical site infections are disproportionately common after colorectal surgery and may be largely preventable. The objective of this retrospective cohort study was to determine the effect of oral antibiotics and mechanical bowel preparation on surgical site infections. What does this paper add to the literature? This is a quality improvement project monitoring our elective colorectal resections for surgical site infections (SSIs) before and after changes in preoperative bowel preparation. Our manuscript a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…However, our study indicated that it was not very common to using oral antibiotics for the bowel preparation of colorectal surgery in China. There are many studies reporting that rectal operations had a higher risk than colectomies [33,34]. Although rectal operations had a lower risk compared with colonic operations in this study, the multivariate analysis revealed that type of surgery was not the independent risk factor (P = 0.182) in Table 4.…”
Section: Discussionmentioning
confidence: 49%
“…However, our study indicated that it was not very common to using oral antibiotics for the bowel preparation of colorectal surgery in China. There are many studies reporting that rectal operations had a higher risk than colectomies [33,34]. Although rectal operations had a lower risk compared with colonic operations in this study, the multivariate analysis revealed that type of surgery was not the independent risk factor (P = 0.182) in Table 4.…”
Section: Discussionmentioning
confidence: 49%
“…In 1972, Nichols et al [ 23 ] introduced a protocol using neomycin and erythromycin with MBP, which reduced the SSI rate from 43% to 9% [ 24 , 25 ]. This protocol proved that the combination of preoperative OA and MBP could synergistically decrease the intestinal bacterial load prior to surgery, thus reducing the contamination of the operative field [ 12 , 26 ]. Multiple trials from the 1970s to the 1990s demonstrated the effectiveness of this approach.…”
Section: History Of Bowel Preparationmentioning
confidence: 99%
“…Multiple trials from the 1970s to the 1990s demonstrated the effectiveness of this approach. However, it was found that systemic antibiotics (SA) with MBP were more effective than OA with MBP [ 26 ].…”
Section: History Of Bowel Preparationmentioning
confidence: 99%
See 2 more Smart Citations